228 Effect of exogenous glucoamylase inclusion on in vitro digestion and feedlot cattle performance. (30th November 2020) - Pittaluga, Alejandro; Yu, Shukun; Li, Wenting; McCann, Joshua C
Abstract: The objective was to evaluate the effect of adding an exogenous glucoamylase (GA) enzyme to a finishing diet on in vitro digestion and performance of feedlot cattle. Experiment 1 evaluated 3 levels of added enzyme (0, 0.24, and 0.72 GA enzyme units) and 2 corn particle sizes (2 and 4 mm) in a 7 h in vitro batch culture fermentation. No interactions were observed (P > 0.10). Addition of GA increased (P < 0.01) in vitro dry matter disappearance by 9%. A smaller corn particle increased (P < 0.01) in vitro dry matter disappearance by 11%. In Experiment 2, Angus × Simmental steers (N = 105; BW = 340 ± 39 kg) were blocked by weight and assigned to 15 pens. Pens were randomly assigned to one of 3 treatments: control (CON) diet with no added enzymes, low inclusion of GA (122 enzyme units/kg DM; LGA), or high inclusion of GA (183 enzyme units/kg DM; HGA). Steers were fed a basal diet consisting of 60% dry rolled corn, 17.5% modified distillers grains with solubles, 12.5% corn silage, and 10% of a corn-based supplement on a DM basis for 139 d. Inclusion of GA did not affect (P ≥ 0.24) final BW, DMI, or ADG overall for the 136 d feeding period. Steers fed HGA had increased (P = 0.02) G:F compared with LGA and CON with least square means of 0.213, 0.194, and 0.197, respectively. Inclusion of GA did not affect (P ≥ 0.19) carcass traits including HCW, 12th rib fat thickness, yield grade, longissimus muscle area, or marbling score. Overall, results suggest inclusion of exogenous glucoamylase enzyme increased in vitro dry matter disappearance in batch culture and improved feed conversion of the finishing diet fed to feedlot steers at 0.381 g enzyme protein/kg DM.